Corporate Tax Avoidance and the Cost of Debt Capital of Listed Manufacturing Companies in Nigeria - Baba, Halima Abdullahi; Muhammad, Muhammad Liman (SEISENSE (PRIVATE) LIMITED, 2023)
Purpose: The study “Tax Avoidance and Cost of Debt Capital in Nigerian Manufacturing Companies” is empirical research that investigates the relationship between tax avoidance and cost of debt capital in Nigerian manufacturing companies.Design/Methodology: The study uses a quantitative research design, which involves the collection of numerical data to test hypotheses. Specifically, the study uses a correlational design to establish the relationship between tax avoidance and cost of debt capital in Nigerian manufacturing companies. The study uses a purposive sampling technique to select 42 Nigerian manufacturing companies listed on the Nigerian Stock Exchange. The study collected secondary data from the annual reports and financial statements of the selected companies for the period 2011–2020.Findings: The results of the empirical analysis include the fact that the cost of debt capital was found to have a strong and positive link with tax avoidance. As a result, tax avoidance is regarded as a symptom of rising information risk in Nigerian manufacturing firms, prompting investors to demand a high rate of return. Total accruals also showed a positive and significant relationship between tax avoidance and cost of debt.Practical Implications: The findings of the study indicate that policymakers may need to implement measures to improve tax enforcement and increase transparency in financial reporting. This could involve increasing resources for tax authorities, strengthening legal frameworks for tax compliance, and promoting better corporate governance practices among companies.